Fit for the Future: An Assessment of the Sustainability Parameters of Liquid Dairy Product Packaging in the DACH Region and the Implications of Upcoming Regulatory Changes - Michelle Klein; Charlotte Neumair; Mattia Primoceri; Manfred Tacker; Silvia Apprich (Foods)
The European Union aims for climate neutrality by 2050 and has proposed the Packaging and Packing Waste Regulation (PPWR) to promote a circular economy, focusing on reducing packaging waste. In this context, a comprehensive sustainability assessment for liquid dairy product packaging, including beverage cartons, bottles and to-go cups, in the DACH region (Germany, Austria and Switzerland) was conducted. The aim was to consider various ecological aspects of environmental impacts and circularity. As the aspect of recyclability is a core aspect in the PPWR, the calculation was of central interest in this project. Here, major differences in the waste management infrastructure between countries could be identified. The majority of assessed packaging falls below the PPWR’s 70% recyclability requirement, with Switzerland showing even lower recyclability due to poor packaging collection and recycling infrastructure. Significant discrepancies in packaging efficiency exist, indicating unnecessary resource consumption, especially in the case of to-go cups. Additionally, the carbon footprint of packaging materials can vary up to ten times within certain product categories, negatively impacting the environment. Good results were identified for the use of certified renewable resources. Overall, the results of the assessment demonstrate several areas for improvement in light of forthcoming regulatory requirements, which must be met in Germany and Austria.